Konsep Mujahadah an-Nafs dalam mengurangi Hyperfocus dan meningkatkan Kualitas Ibadah pada Penderita ADHD (Attention Deficit Hyperactivity Disorder) - Refa Adinda Fauziah Isni (Gunung Djati Conference Series, 2023)
In general, not many peope are aware of the importance of mental health. Parents often ignore the small symptoms of mental illness that appear on their child, even though these symptoms are signs for parents to provide appropriate treatment to prevent mental illness from getting worse in the future. It cause many teenagers and adults today have serious mental illness due to lack of mental health care as a chid, one of them is ADHD. Common symptomsof ADHD in DSM-5 include hyperactivity, impulsivity, difficulty concentrating or easily distracted.however, a less well-known symptom is hyperfocus, which is when the patient expriences a condition where they are excessively obsessed and fixated on something that interest them The way to overcome hyperfocus on ADHD is not to cause prolonged adverse effects, so this article takes the concept of mujahadah an-nafs as a solution to reduce the intensity of hyperfocus in ADHD. Methodologies of research in this article is a kind of qualitative with a focus on qualitative descriptive, cause researchers want to study and expose the results of this article so that the reader can understand the urgency of the problem focused on the research discussion. This data collection technique used in this research is literature study techniques and observation techniques. The aim of the study was to see the influence of mujahadah an-nafs in reducing the intensity of hyperfocus in people with ADHD and increase the quality of worship. By placing the concept of mujahadah an-nafs on thoses who have ADHD through several meetings can produce a reasonable result, the respondents had an understanding of theirself, what problems they had, solutions to offer, and how to execute those solutions so that the problem they had was solved. In this way, the concept of mujahadah an-nafs succeeded in becoming one of the solutions to ADHD with hyperfocus disorders and in wanting to improve the worship quality.